Transcatheter arterial embolization for intercostal arterio-esophageal fistula in esophageal cancer - Tetsuya Tajima; Shigeo Haruki; Shinsuke Usui; Koji Ito; Akiyo Matsumoto; Akiyuki Matsuhisa; Noriaki Takiguchi (Surgical Case Reports)
Abstract Background While esophageal fistula formation in the adjacent organs is associated with high rates of morbidity and mortality, the management of non-aortic arterio-esophageal fistula has not been frequently reported. Case presentation A 69-year-old Japanese man who had undergone definitive chemoradiotherapy for esophageal cancer was admitted to our hospital with hematemesis. He was diagnosed with mediastinal abscess caused by esophageal perforation, and esophageal bypass surgery was performed. After 3 days, he presented with fatal hemoptysis. As angiography revealed an intercostal artery pseudoaneurysm, transcatheter arterial embolization was performed. Conclusions When patients with esophageal cancer, especially those with a history of radiotherapy and/or mediastinitis, present with hematemesis and/or hemoptysis, the possibility of non-aortic arterio-esophageal fistula should be considered. Transcatheter arterial embolization is an effective treatment for non-aortic arterio-esophageal fistula.